Gender in modern India history, culture, marginality - Singh, Lata 1960-; Sinha, Shashank Shekhar (Oxford University Press, 2024)
'Gender in Modern India' brings together research on a range of themes, including masculinity and sexuality; social reforms, castes, and contestations; Adivasis, patriarchy, and colonialism; capitalism, political economy, and labour; health, medical care, and institution building; culture and identity; and migration and its new dynamics